Molecular analyses of two bacterial sampling methods in ligature-induced periodontitis in rats - Fontana, Carla Raquel [UNESP]; Grecco, Clovis; Bagnato, Vanderlei Salvador; de Freitas, Laura Marise [UNESP]; Boussios, Constantinos I.; Soukos, Nikolaos S. (Wiley, 2018)
The prevalence profile of periodontal pathogens in dental plaque can vary as a function of the detection method; however, the sampling technique may also play a role in determining dental plaque microbial profiles. We sought to determine the bacterial composition comparing two sampling methods, one well stablished and a new one proposed here. In this study, a ligature-induced periodontitis model was used in 30 rats. Twenty-seven days later, ligatures were removed and microbiological samples were obtained directly from the ligatures as well as from the periodontal pockets using absorbent paper points. Microbial analysis was performed using DNA probes to a panel of 40 periodontal species in the checkerboard assay. The bacterial composition patterns were similar for both sampling methods. However, detection levels for all species were markedly higher for ligatures compared with paper points. Ligature samples provided more bacterial counts than paper points, suggesting that the technique for induction of periodontitis could also be applied for sampling in rats. Our findings may be helpful in designing studies of induced periodontal disease-associated microbiota.
Keywords: biofilm, periodontal pathogens; molecular diagnostics; sampling technique